The Development of a Webtoon-Based Digital Comic Entitled “Was machst du?” for Enhancing A2-Level German Reading Skills (International Journal of Education and Literature, 2025)
This study aims to develop an instructional medium in the form of a Webtoon-based digital comic entitled “Was machst du?”, adapted from the Netzwerk neu A2 textbook, to enhance German reading comprehension at the A2 level. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). Validation was conducted by two experts one in content and one in media with validation scores of 91% and 92%, respectively, indicating that the comic is highly suitable for instructional use. A limited trial was carried out among students of the German Language Education Program at Universitas Negeri Medan. The results showed that the comic supported students’ reading comprehension, increased motivation, and reduced reliance on online translators. This study concludes that integrating official textbook content into digital comic formats published through popular platforms such as Webtoon represents an effective and relevant innovation for digital-native learners.